Obliczanie Płyt Siatkowych na Podstawie Teorii Efektu Brzegowego - Konieczny, S.; Woźniak, C. (Engineering Transactions, 1967)
In the equations of the continual theory of lattice-type plates [1] a small parameter is involved. In the displacements equations the differential operator of a higher order appears. This shows the possibility of an asymptotic treatment of boundary-value problems. This paper discusses the simplest variant of such an approach, in which the accurate set of differential equations is replaced by a system composed of a fourth order equation and a certain algebraic equation. Then, the order of the set of equations remains unchanged, which enables accurate satisfaction of all the three boundary conditions. The paper contains also a computation example of a lattice-type plate, illustrating the theory presented.